PERBANDINGAN MODEL BUSINESS MODEL CANVAS DENGAN LEAN CANVAS PADA STARTUP PIECEWORK - I Putu Deddy Surya Mahendra (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Piecework is a startup engaged in the social media agency that focuses on helping small businesses develop business in the era of globalization. In developing a startup, it is necessary to have the right business model for a basic description of a company's business idea. At first the Business Model Canvas was a business model that was often used by startups, but after the development of Lean Canvas, startups were interested in using it for startup development. Comparison of Business Model Canvas and Lean Canvas in Piecework startup serves to improve the startup development strategy, get a better position in the market, to better understand about the business framework based on both business models. The method used is qualitative by conducting interviews with 10 informants to validate the problems experienced. From the comparison of the Business Model Canvas and Lean Canvas business models, it can be concluded that Lean Canvas is considered more appropriate to use Piecework because with Lean Canvas Piecework can design services that are more appropriate for consumers.